Contributions in the scope of the psychology of the learning - Meza B., Anibal (2010)
The author examines his own bibliographic production in learning psychology area. Each of four publications is examined according to: (a) circumstances of its origin and elaboration, (b) main traits in respected to other Peruvian publications of same subject, (c) its contents, including how it is organized and topics, and, (d) probable contributions to knowledge on learning psychology in Peru and probable projections to professional practice.